2016
DOI: 10.1371/journal.pone.0153711
|View full text |Cite
|
Sign up to set email alerts
|

Who Has Mycobacterial Disease? A Cross Sectional Study in Agropastoral Communities in Tanzania

Abstract: ObjectiveTo determine and describe clinical symptoms, demographic characteristics and environmental exposures as determinants of pulmonary mycobacterial diseases among patients examined for tuberculosis in agropastoral communities in Northern Tanzania.MethodsThis was a cross sectional study. Sputum samples were collected from patients attending three hospitals in Tanzania, and were investigated for pulmonary tuberculosis by microscopy between November 2010 and June 2012. The patients were interviewed about bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
9
2
Order By: Relevance
“… 25 , 26 Although this study did not conduct drug sensitivity testing, both M. fortuitum and M. abscessus can be misdiagnosed as resistant TB/multidrug-resistant TB due to their natural resistant pattern to antituberculosis drugs, 15 , 26 which may result in unnecessary administration of toxic second-line anti-TB treatment. The prevalence of NTM reported in the present study, which seems to be lower than recently reported in the country, 12 , 22 is not conclusive because of the limited sample size and because it only constitutes a small proportion of pulmonary TB diagnosis scenarios. Moreover, due to the retrospective nature of this study, we could not certainly implicate the isolated NTM as the cause (and the only cause) of the infection in these patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 25 , 26 Although this study did not conduct drug sensitivity testing, both M. fortuitum and M. abscessus can be misdiagnosed as resistant TB/multidrug-resistant TB due to their natural resistant pattern to antituberculosis drugs, 15 , 26 which may result in unnecessary administration of toxic second-line anti-TB treatment. The prevalence of NTM reported in the present study, which seems to be lower than recently reported in the country, 12 , 22 is not conclusive because of the limited sample size and because it only constitutes a small proportion of pulmonary TB diagnosis scenarios. Moreover, due to the retrospective nature of this study, we could not certainly implicate the isolated NTM as the cause (and the only cause) of the infection in these patients.…”
Section: Discussioncontrasting
confidence: 99%
“… 10 , 20 NTM infections present similar clinical and radiographic manifestations like those of pulmonary TB, 7 , 21 hence resulting false in positives in both smear and culture. In Tanzania, it is commonly assumed that patients presenting with pulmonary infection are infected with MTB, 12 , 22 , 23 with the possibility of other respiratory infection like NTM infection not taken into consideration. In this study, 3 patients (3.19%) were confirmed as having NTM infections (2 M. fortuitum and M. abscessus ), but they may had been mistreated as pulmonary TB, which may result in worsening patient’s health, repeated visits to health facilities, and an increase in the risk of drug-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the use of suboptimal diagnostic tests, particularly in developing countries like Tanzania. The detection of acid-fast bacilli by smear examination of NTM can result in the misdiagnosis of TB cases (Hoza et al, 2016a,b;Mfinanga et al, 2014;Kilale et al, 2016;Mnyambwa et al, 2017a), which normally do not respond to anti-TB drugs, thereby leading to classification as MDR-TB (Lu et al, 2016;Shahraki et al, 2015). Most of the MAC members are naturally resistant to anti-TB drugs (Shahraki et al, 2015;Mpagama et al, 2013), which leads to the unnecessary administration of toxic second-line anti-TB treatments, thereby increasing the risk of the evolution of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also revealed that members of M. yongonense Type I genotype harbour a unique DNA mismatch repair gene MutS4 family, that potentially serves as a putative driving force for the suggested HGT between the M. parascrofulaceum and M. yongonense Type I genomes through homologous recombination events (Kim et al, 2017). The occurrence of NTM in Tanzania has been reported frequently (Hoza et al, 2016a,b;Mfinanga et al, 2014;Kilale et al, 2016;Mnyambwa et al, 2017a), but characterization of the isolates has relied on suboptimal typing methods that have potentially hindered accurate species identification.…”
Section: Introductionmentioning
confidence: 99%
“…The NCBA assay has the following advantages compared to SSM, culture or PCR-based methods: (a) homogenization and liquefaction of sputum sample eliminates non-mycobacterial cellular materials [ 20 ]; (b) it ensures the detection and concentration of Mtb cells in highly endemic regions; (c) it is a fast and straightforward technique, providing results in a few minutes; and (d) it has a reduced cost, since it uses the same equipment and infrastructure available for performing SSM. In spite of not being exclusive and specific to Mtb , the glycan–glycoprotein interaction allows the capture of AFB in symptomatic respiratory patients in TB-endemic regions because other mycobacteria are less frequently detected in sputum samples [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%